Pengungkapan Sustainability Reporting Dalam Pelaksanaan Corporate Social Responsibility Di PT Bank BJB - Mohammad Haidar Wahda Gustam Gustam; Minto Yuwono (Journal of Knowledge Management, 2024)
This research aims to analyze the disclosure of Sustainability Reporting in the implementation of Corporate Social Responsibility (CSR) at PT Bank Pembangunan Daerah Jawa Barat dan Banten (BJB). In the context of regulations stipulated by Law Number 25 of 2007, CSR is expected to be a responsibility that is not only legal in nature but also reflects the company's commitment to society and the environment. Through a qualitative approach, this study evaluates BJB's sustainability reports from 2019 to 2023, focusing on environmental, social, and economic aspects. The analysis results indicate that BJB has demonstrated significant improvement in disclosing sustainability performance, including a reduction in carbon emissions and contributions to the Sustainable Development Goals (SDGs). Furthermore, this research highlights the importance of transparency and accountability in the implementation of CSR, as well as the positive impacts generated for society and the environment. These findings affirm that the disclosure of sustainability reports serves not only as a communication tool but also as a means to build trust between the company and its stakeholders